Free versus fee-based for information access - Valdez, Andriette S. (Institute of Library Science, University of the Philippines Diliman, 2001)
This study aimed to determine the viability of fee-based information services in the UPLB Libraries. Traditional library services being offered free, are more popular and heavily utilized by the users. Specifically the objectives of the study were: 1) to determine the adequacy of available fee-based information services to meet the academic and research need of the users; 2) to know the problems encountered in offering fee-based information services; 3) to determine the marketing strategies employed to promote use of fee-based information services; 4) to know the implications of offering fee-based information services in the UPLB libraries.